2019
DOI: 10.1088/1755-1315/289/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization the geotechnical properties of a Malaysian granitic residual soil grade V

Abstract: Residual soils are produced from weathering of rocks and commonly found in tropical humid areas. The geotechnical properties of residual soils are a function of the parent rock, the degree of weathering, and climate which vary from region to region. A thorough quantification of the geotechnical characteristics of residual soils is required for a safe and economic structure design. This study attempts to summarize a series of important geotechnical properties of a Malaysian granitic residual soil grade V which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…Permukaan batuan granit mengalami proses luluhawa yang tinggi, menghasilkan tanah baki. Keadaan ini sesuai untuk berlakunya tanah runtuh (Hirata & Chigira 2019;Saffari et al 2019;Wu et al 2022). Lapisan tanah baki tebal meliputi lebih daripada 80% kawasan tanah di Malaysia (Saffari et al 2019), lebih daripada 75% permukaan di Malaysia diliputi oleh tanah baki terurai daripada granit, sedimen dan metasedimen serta lebih kurang 50% permukaan tanah di Semenanjung Malaysia terdiri daripada batuan granit (Abdul Samad et al 2018).…”
Section: Pengenalanunclassified
“…Permukaan batuan granit mengalami proses luluhawa yang tinggi, menghasilkan tanah baki. Keadaan ini sesuai untuk berlakunya tanah runtuh (Hirata & Chigira 2019;Saffari et al 2019;Wu et al 2022). Lapisan tanah baki tebal meliputi lebih daripada 80% kawasan tanah di Malaysia (Saffari et al 2019), lebih daripada 75% permukaan di Malaysia diliputi oleh tanah baki terurai daripada granit, sedimen dan metasedimen serta lebih kurang 50% permukaan tanah di Semenanjung Malaysia terdiri daripada batuan granit (Abdul Samad et al 2018).…”
Section: Pengenalanunclassified
“…𝐺 𝑠 𝛾 𝑤 𝛾 𝑑 (1) The porosity (n) of residual soil is described as the number of pore spaces in a soil mass and it is primarily influenced by the soil structure. The soil porosity was calculated from the void ratio (e), as follows:…”
Section: 𝑒 =mentioning
confidence: 99%
“…The weathering process has resulted in soil heterogeneity, which is common to residual soil, and this type of soil accounts for more than 75 % of the surface deposits in Peninsular Malaysia [1,2]. Soil heterogeneities in tropical residual soil consist of weaker materials due to the weathering process.…”
Section: Introductionmentioning
confidence: 99%
“…In the soils, matter and energy exchange with the atmosphere, biosphere, and hydrosphere [2]. The speed of weathering for the formation of soil and the percentage of fine particles are the two crucial factors that can affect the geotechnical properties of soils [3]. Soils are naturally occurring materials that play a vital role in the design, construction, and performance of civil engineering structures.…”
Section: Introductionmentioning
confidence: 99%
“…The oldest one was proposed by Terzaghi et al [12], where clay is classified as soft soil when the unconfined compressive strength is less than 50 kPa. Das [13] suggested that a void ratio of soft soil is in the range of 0.9-1.4, and the dry unit weight ranges from 11.5-14.5 kN/m 3 . Soft soil has a coefficient of permeability that is less than 1.0 × 10 −7 m/s, according to Kempfert and Gebreselassie [14].…”
Section: Introductionmentioning
confidence: 99%